(untitled) (Agroindustria, Sociedad y Ambiente, 2001)
Pine resin is a substance rich in mono and diterpenes, susceptible to polymerization reactions, which can be separated into two fractions: turpentine and rosin, which are widely used in the formulation of products, mainly in the adhesives industry, inks, tires, pharmaceutical, etc. Previous research has developed a resining method that does not alter the ultrastructure characteristics of Venezuelan Pino Caribe. In that sense, it is important to determine and evaluate the available technologies for obtaining turpentine and rosin. For this, a technological intelligence work was developed through the search and analysis of patents, where it was identified that steam distillation combined with stripping columns is the most developed, highlighting China and the United States as leading countries. This information can contribute to the decision making that will drive the development of the Forest Industry in our country.